A5 FRUCTOOLIGOSACCHARIDE EXACERBATES INFLAMMATION AND THE LOSS OF MICROBIAL DIVERSITY FOLLOWING ILEOCECAL RESECTION IN A MURINE MODEL OF POST-OPERATIVE CROHN'S DISEASE RECURRENCE. (1st March 2018) - Laffin, M; Perry, T; Hotte, N; Park, H; Fedorak, R; Dicken, B; Madsen, K
Abstract: Background: Fructooligosaccharide (FOS) is a fermentable prebiotic that stimulates the growth of bifidobacteria which has been shown to have anti-inflammatory activity. Individuals with Crohn's disease frequently require ileocolic resection (ICR), and disease often recurs in the neo-terminal ileum following surgery. Previously we have shown that ICR in a mouse model induces gut dysbiosis, a depletion of anaerobic microbes, including bifidobacteria, and an increase in ileal inflammation. Aims: We hypothesized supplementation of a post-ICR diet with FOS in a mouse model would be effective in stimulating the growth of bifidobacteria and thus reducing systemic and local inflammation. Methods: ICR was performed in IL10-/- mice (129S1/SvlmJ) with established colitis. Following surgery, mice were subsequently fed a chow diet ± 10% FOS for 28 days (n=11), alongside diet-matched non-ICR control groups (n=11). Serum, colon, and terminal ileum (TI) were analyzed for cytokine expression by a MesoScale discovery platform. DNA extracted from stool was analyzed using 16s rRNA sequencing and qPCR. Expression of tight junction genes occludin and ZO1 was assessed using qPCR. Short-chain fatty acids (SCFA) concentrations were assessed using high-pressure liquid chromatography. Results: A precipitous decrease in fecal bifidobacteria and bacterial diversity was seen following ICR (p<0.05). ICR also led to increased serum inflammatory cytokines (IL-2, IL-12, IL-4) (p<0.05) and a complete depletion of fecal butyrate (p<0.01). FOS-supplementation resulted in an increase in the relative amount of bifidobacteria and fecal acetate (p<0.01). However, contrary to our hypothesis, the FOS diet exacerbated post-operative systemic inflammation (elevated serum IL-6 p<0.05), ileitis (elevated IL-1β p<0.1) and colitis (elevated IFNγ and TNFα p<0.05). FOS-supplementation was not able to reverse the obliteration of fecal butyrate following ICR. Expression of o ccludin and ZO1 was reduced in FOS-supplemented mice (p<0.05). FOS supplementation exacerbated the loss of bacterial diversity following ICR and there was a correlation between loss of diversity and bifidogenic effectiveness of FOS in promoting bifidobacteria growth (r= -0.61, p<0.05). Conclusions: FOS-supplementation of a post-ICR diet resulted in a decrease in fecal bacterial diversity, reduction in barrier function, and increased inflammation. We speculate that providing high amounts of a targeted substrate allowed for the expansion of bifidobacteria's niche, enabling a bloom of acetate-producing organisms which consequently hindered the growth of butyrate–producing anaerobic organisms necessary for gut homeostasis. Funding Agencies: None